Does The EFL-Multimodal Textbook and Culture In The Independent Curriculum Represent Character Education?: A Critical Discourse Analysis - Dihliza Basya; Siti Nur Halizah; Nur Diawati (Penerbit STKIP PGRI Bangkalan, 2025)
While there has been extensive research on Critical Discourse Analysis (CDA) in multimodal textbooks, most studies primarily focus on analyzing culture and gender. However, the investigation of Character Education using CDA still needs to be more extensive. To fill this void, this study aims to examine the representation of Character Education in secondary-level English textbooks in Indonesia, following one of the goals of the latest curriculum to make each individual have character and behave following the values of Profil Pelajar Pancasila (The Pancasila Students’ Profiles). To address this issue, this study conducted a critical discourse analysis by adopting Kress and Van Leuween's (2006) Visual Grammar Theory to analyze the visual image and Halliday’s (1975) and Matthiessen’s (2004) Systemic Functional Analysis (SFL) to elucidate the textual representation of the character education in the selected EFL-multimodal textbook. This research focuses on Thomas Lickona's (1996) six fundamental components of good character: caring, honesty, fairness, accountability, and respect for self and others. This study can assist educators in incorporating character education into their teaching techniques and provide them with the essential skills and information to foster the development of positive character traits in their students.